Cardiovascular Risk Reduction in the Workplace With CAMMPUS (Cardiovascular Assessment and Medication Management by Pharmacists at the UBC Site). Issue 6 (June 2019) - Gobis, Barbara; Kapanen, Anita I.; Reardon, Jillian; Min, Jason; Li, Kathy H.; Lynd, Larry D.; Zed, Peter J.
Background: Cardiovascular (CV) disease is a leading cause of death despite being largely preventable. Employers increasingly offer preventive health programs in the workplace, and pharmacists are well suited to provide these programs.Objective: To evaluate the impact of a pharmacist-led service on CV risk in University of British Columbia (UBC) employees.Methods: This was a prospective observational pre-and-post design study, with participants as their own controls. Employees >18 years of age in the UBC health plan with a Framingham Risk Score (FRS) ≥10% or ≥1 medication-modifiable CV risk factor were included. Participants received a baseline assessment, individualized consultation for 12 months, and a final assessment by a pharmacist at the UBC Pharmacists Clinic. The primary end point was FRS reduction.Results: Baseline assessment of 512 participants between September 2015 and October 2016 yielded 207 (40%) participants, of whom 178 (86%) completed the 12-month intervention. Participants were 54% female and 55% Caucasian, with an average age of 51 (SD = 9.1) years. FRS at baseline was <10 in 45.8%, 10 to 19.9 in 37.9%, and ≥20 in 16.4% of participants. Over 12 months, significant reductions in average FRS (from 11.7 [SD = 7.7] to 10.7 [SD = 7.3]; P = 0.0017) and other parameters were observed. Significant improvements in quality of life (EQ5D change of 0.031 [95% CI = 0.001, 0.062] P = 0.023) and medication adherence (MMAS-8 change of 0.42 [ P = 0.019]) were also noted.Conclusions and Relevance: UBC employees had improvements in health markers, self-reported quality of life, and medication adherence after receiving a 12-month pharmacist-led intervention. Pharmacists are encouraged to provide CV risk reduction services in workplaces.